(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
There is unambiguous evidence from the two small excavation areas on the stack for intensive Neolithic use of the site in the form of ceramics, lithics and a truncated posthole. The Iron Age deposits yielded only a small number of diagnostic finds though radiocarbon dates provide a date range of 210-50 cl BC.